ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE SISTEM INFORMASI JARINGAN PENGELOLA (SIGAP) PADA PDDIKTI MENGGUNAKAN METODE DESIGN THINKING - Ramla Shantika Devi (2022)
The Higher Education Database (PDDIKTI) has a helpdesk website, namely the Management Network Information System (SIGAP) application, which is used as a helpdesk service. Helpdesk has facilities with support tickets between admins and users, as a medium for easy direct message communication. However, in the helpdesk service process there were several obstacles such as the accumulation of helpdesk tickets and after an analysis of the running system, several problems were found, including difficulty finding information, a less responsive helpdesk admin, and so on. Therefore, this study was conducted to analyze user experience as an evaluation of the website that is already running. The methods in this study are the System Usability Scale (SUS) and the Design Thinking Method as redesign stages. Based on the results of the current system analysis research, the results of the evaluation score of 55 were obtained and after redesign and testing usability, it was found that the assessment score increased by 78 or an increase of 41.8%. Thus it is known that there have been positive changes to the results of the redesign that have been carried out. Keywords : Redesign, SIGAP, usability, System Usability Scale (SUS), dan Design Thinking.